Methodological questions of creation the budgeting system at the enterprise - L. A. Reshetnyak; Yu. I. Zdorovets (Путеводитель предпринимателя, 2020)
The formation of optimal and effective budgeting system depends, among other things, the timely and correct decision of organizational questions at the initial stage of the formation process.